IDENTIFIKASI PENGETAHUAN DAN KETERAMPILAN PERLINDUNGAN DIRI ANAK DARI PELECEHAN SEKSUAL DI SD MUHAMMADIYAH 1 SURAKARTA - Murfiah Dewi Wulandari; Andina Widhayanti; Achmad Fathoni; Muhammad Abduh; Muhamad Taufik Hidayat (Profesi Pendidikan Dasar, 2019)
The purposes of this research are to 1) identify knowledge of children's personal protection from sexual abuse; 2) identifying children's personal protection skills from sexual abuse; and 3) describe efforts to prevent sexual abuse that have been carried out by the school. This type of research is descriptive qualitative research. This research was conducted at SD Muhammadiyah 1 Surakarta. The research subjects were fifth grade students. The technique of collecting data are through observation, interviews, and documentation. Qualitative data analysis techniques use the concepts conveyed by Miles and Hubermen. The validity of the data was obtained through source triangulation and technical triangulation. The results of the research indicate that 1) the child's ability to identify appropriate touch situations is good and the child's ability to identify touch situations that are not appropriate is very good. This are indicated by the child knowing that the appropriate touches such as the touch of the parents when caring for the body, the touch of doctors and nurses when examining the disease and inappropriate touches such as the touch of a housemaid or neighbor; 2) the child's knowledge and skills in reporting are very low, this are indicated by the child being unable to tell other people and children protect themselves by shouting, angry and running; 3) school prevention efforts have been carried out by schools through health education on reproduction and puberty in two stages, namely in the health and religious.